Understanding Federal Student Loan Repayment. (June 2015) - Johnson, Carrie
<x xml:space="preserve">Abstract</x> The purpose of this study was to explain the federal student loan repayment process. Individuals with a college degree earn more over their lifetime than those without a college degree. However, the price of a college education has increased substantially and 69% of college graduates in 2012 had student loans to repay. There are eight federal repayment plans that may lead to confusion for borrowers. Education is needed to assist borrowers in making informed repayment decisions. Educators at postsecondary institutions have an opportunity to provide education to students.